Pengaruh Motivasi dan Disiplin Kerja terhadap Kinerja Karyawan Baznas Se-Jatim - Lia Amalia; Achmad Daengs GS (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to determine and analyze the extent to which motivation and work discipline affect the performance of BAZNAS employees throughout East Java. Data were obtained by distributing questionnaires to 88 respondents using a descriptive quantitative approach. The data analysis technique employed was statistical analysis through multiple linear regression tests. The results of the study indicate that both motivation and work discipline, both partially and simultaneously, have a significant effect on the performance of BAZNAS employees throughout East Java. This finding is supported by the results of simultaneous tests (F-tests) and partial tests (t-tests), which show the significance values of the two independent variables that support the research hypothesis. Specifically, motivation was found to positively influence employee performance, while work discipline also played a key role in enhancing the performance of employees. The findings suggest that when employees are motivated and disciplined in their work, their performance tends to improve. These results are important for management, as they imply that to enhance employee performance, BAZNAS should focus on both increasing motivation through various incentives and improving work discipline by establishing clear rules and monitoring mechanisms. In conclusion, this study confirms that there is a joint influence between motivation and work discipline on the performance of BAZNAS employees throughout East Java, indicating that both factors are essential in driving organizational success